Steps for Preparation of Reading Materials Product "Kumpulan Cerpen Emansipasi Wanita” (Collection of Women's Emancipation Short Stories) in Sara’s Perspective and Its Implementation as Reading Material on 10th Grade Students of MAN Insan Cendikia, East Aceh, Indonesia - Intan Novita; Biner Ambarita; Malan Lubis (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
Reading material is one of the tasks that the teacher must do. Reading material that has an attraction for students will motivate students to read the text seriously, which in turn will support the students' reading comprehension. Reading is the most interesting thing among students, moreover reading material is very much needed for students and can add references in the school library. MAN Insan Cendikia, East Aceh does not yet have literary material. Reading material in MAN Insan Cendikia, East Aceh school is only in the form of reading about science not in the form of literature. The material expert validation stage obtained results from these assessments indicating that the feasibility aspects of the material content of reading material products were declared 86.71% with the category "Excellent". The contents are declared feasible because they are in the average value above 75% with the category "Good".